Development of A Chemistry Teaching Module on Acids and Bases Based on Subulussalam Local Wisdom : Exploration of Batik, Bauh Buluh Fish, and Nakan Lancing - Fitri, Desi Ely; Khaldun, Ibnu; Hasan, M.; Zulfadli, Zulfadli; Nazar, M.; Mentari, Mentari (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop a chemistry teaching module that integrates the local wisdom of Subulussalam, incorporating cultural elements such as Subulussalam batik, ikan bauh buluh, and nakan lancing, and to evaluate the responses of students and teachers to the module. The module is designed to contextualize acid-base chemistry concepts through local cultural practices, thereby making learning more meaningful and relevant. The research employs a Research and Development (R&D) approach, utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data collection is conducted through closed-ended questionnaires, and the data are analyzed using both quantitative and descriptive techniques. The module undergoes validation by experts in chemistry and instructional media and is tested on a sample of 66 students and 4 teachers. The results indicate that the chemistry teaching module based on Subulussalam local wisdom is both effective and relevant, as perceived by students and teachers. The integration of local content, such as Subulussalam batik, ikan bauh buluh, and nakan lancing, successfully links chemical concepts to students' real-life experiences, facilitating their understanding of abstract material. Furthermore, the module enhances learning motivation, argumentation skills, and scientific and cultural knowledge. Notably, learning based on local wisdom fosters cultural pride and strengthens global diversity character, aligning with the values of the Pancasila Student Profile and the Merdeka Curriculum. Consequently, this module not only teaches chemistry but also serves as a medium for character education, cultural preservation, and meaningful, contextual learning.